Zinc oxide films prepared by sol–gel spin coating technique - Kamaruddin, Sharul Ashikin; Chan, Kah Yoong; Yow, Ho Kwang; Sahdan, Mohd Zainizan; Saim, Hashim; Knipp, Dietmar (Springer Berlin Heidelberg, 2011)
Zinc oxide (ZnO) thin films and micro- and nanostructures are very promising candidates for novel applications in emerging thin-film transistors, solar cells, sensors and optoelectronic devices. In this paper, a low-cost sol-gel spin coating technique was used to fabricate ZnO films on glass substrates. The sol-gel fabrication process of the ZnO films is described. The influence of precursor concentration on the material properties of the ZnO films was investigated. Atomic force microscopy and X-ray diffractometry were employed to examine the structural properties of the ZnO films. The optical properties of the ZnO films were characterized with ultraviolet-visible spectroscopy. The experimental results reveal that the precursor concentration in the sol-gel spin coating process exerts a strong influence on the properties of the ZnO films. The effects of the precursor concentration are discussed. Document Type: Article